2021
DOI: 10.1111/epi.16872
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance‐guided laser interstitial thermal therapy: Correlations with seizure outcome

Abstract: This study was undertaken to identify clinical factors associated with seizure freedom after magnetic resonance-guided laser interstitial thermal therapy (MRgLiTT) in temporal lobe epilepsy patients with unilateral mesial temporal sclerosis (MTS). Methods: We identified 56 patients with magnetic resonance imaging-defined MTS who underwent MRgLiTT with at least 1 year of follow-up. Primary outcome was seizure freedom at 1 year. We examined the association of seizure freedom and the following clinical factors: a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In our study, these two variables were associated with a Class I outcome on univariate (but not multivariate) analyses. Of note, Kang et al 31 also found that older age at the time of surgery was associated with a Class I outcome after an LiTT.…”
Section: Discussionmentioning
confidence: 96%
“…In our study, these two variables were associated with a Class I outcome on univariate (but not multivariate) analyses. Of note, Kang et al 31 also found that older age at the time of surgery was associated with a Class I outcome after an LiTT.…”
Section: Discussionmentioning
confidence: 96%
“…However, previous studies have suggested how the presence of selected electrographic characteristics may be associated with seizure outcome. For example, the presence of preoperative bilateral temporal interictal discharges, 56 tonic–clonic seizures, 57 and interictal temporal delta slowing 58 have been shown to be predictive of seizure outcomes. Only a limited number of patients had documentation of this electrographic information available, and therefore were not included in our analysis as a covariate.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is a vast literature on postoperative outcome reports, showing that seizure freedom is only achieved in 60–65% of patients in whom mesiotemporal epilepsy surgery is performed [e.g., 6 , 7 ], including selective approaches like LITT [ 2 ], clearly showing that there is a need to improve patient selection for selective mesiotemporal interventions and to differentiate this group from seizure origin in other brain regions with similar electroclinical features. It is a misunderstanding of our publication that 100% of patients with mesiotemporal seizure origin when operated become seizure free—this gold standard of postoperative seizure freedom for correct localization of the epileptogenic zone was an inclusion criterion for the comparator group with mTLE rather than an outcome report.…”
mentioning
confidence: 99%